2019
DOI: 10.3389/fpsyg.2019.01643
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Ethnic Stereotypes and Their Antecedents in Russia: The Stereotype Content Model

Abstract: The stereotype content model (SCM), originating in the United States and generalized across nearly 50 countries, has yet to address ethnic relations in one of the world’s most influential nations. Russia and the United States are somewhat alike (large, powerful, immigrant-receiving), but differ in other ways relevant to intergroup images (culture, religions, ideology, and history). Russian ethnic stereotypes are understudied, but significant for theoretical breadth and practical politics. This research tested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(77 citation statements)
references
References 88 publications
2
65
0
10
Order By: Relevance
“…Moreover, they have argued that the mean level differences in reported stereotypes between different responses instructions might not under all circumstances reflect the relative position of different target groups within the two-dimensional stereotype content space ( Kotzur et al, 2020 ). Even small differences in the mean level of reported stereotypes can be indicative of the distinctive social perceptions and behaviors toward members of different target groups, with some groups (including the Roma) being outliers within their particular SCM quadrant (see e.g., Grigoryev et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, they have argued that the mean level differences in reported stereotypes between different responses instructions might not under all circumstances reflect the relative position of different target groups within the two-dimensional stereotype content space ( Kotzur et al, 2020 ). Even small differences in the mean level of reported stereotypes can be indicative of the distinctive social perceptions and behaviors toward members of different target groups, with some groups (including the Roma) being outliers within their particular SCM quadrant (see e.g., Grigoryev et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, surveys conducted in Russia have demonstrated that the power stereotypes of Jews are widespread in this country (Gibson & Duch, 1992;Gibson & Howard, 2007;Korey, 1972;Leach et al, 2008). In a recent study that investigated stereotypes of 60 different ethnic groups in Russia, Jews were among the five groups highest in the competence index (Grigoryev et al, 2019). Content of the power stereotype permits us to assume that it is related to the power values and to the motivation to establish control over other people and material and social resources in terms of Schwartz's value theory (Schwartz et al, 2012).…”
Section: Powermentioning
confidence: 98%
“…Second, some stereotypes formulated in terms of personality traits assume that the stereotyped group has a specific motivational goal. For instance, when a group is stereotyped as low on the warmth dimension, it is assumed that members of this group are motivated to harm members of the stereotyping group (Grigoryev et al, 2019;Yzerbyt, 2016). Some other stereotypes formulated as traits assume that members of the stereotyped group have especially high or low preference for specific values.…”
Section: Values and Stereotypesmentioning
confidence: 99%
See 1 more Smart Citation
“…A detailed analysis of the barriers to integration created by ethnic cultural differences was carried out on the basis of studying the evolution of interethnic marriages in society, as one of the productive strategies of social integration [1]. Among the important conclusions of the researcher, consonant with the opinion of a number of scholars, a decrease in the cultural distance between the indigenous population and immigrants ensures the socio-economic well-being of the territory [2,3,4,5,6,7,8].…”
Section: Literature Reviewmentioning
confidence: 99%